Minimization of Sodium in Iranian White Brined Cheese - Ashrafi, Roghieh; Rezazad Bari, Mahmood; Khosroshahi, Asghar; Alizadeh, Mohammad (Asian Journal of Chemistry, 2010)
A chemometric approach was used to minimize NaCl content in Iranian white brine cheese. Influence of different ratios of NaCl:KCl and ripening time on sodium and potassium content, proteolysis, lipolysis, dry matter, TVC, mold count and sensorial quality was explored using a mixture design. Partial substitution of NaCl by KCl did not influence the extent of proteolysis, lipolysis and dry matter. Sodium content of the cheese samples decreased by increasing KCl concentration in brine. Ripening time had positive effect on both Na and K content of the cheese samples. Increasing in KCl concentration in brine had significantly negative effect on TVC and mold. All cheeses were free from Coliform. NaCl and KCl concentrations in brine were effective factors on sensory score. After modelling of Na and K variations and regarding sensory score and dry matter the optimum condition for minimization of Na in Iranian white brine cheese were: concentration of KCl and NaCl in brine were respectively 27.1 and 72.9 % and ripening time of 40 d. Na and K contents in the cheese samples made at optimum condition predicted to be 2.43 and 1.32 %, respectively. KCl at concentrations more than 27.7 % led to significantly low acceptability.